GE_GERICHTE A/1770/2023 vom 11. Dezember 2024 - GE Cour de justice (2024)
TAXATION CONSÉCUTIVE À UNE PROCÉDURE;SOUSTRACTION D'IMPÔT;CHARGES COMMERCIALES(DROIT FISCAL) | LIFD.151.al1; LPFisc.59.al1; LIPM.12.leth; LIFD.58.al1.letb; LIFD.175.al1; LPFisc.69.al1